Leadership Communication Style and Teacher Work Culture towards Collaborative Management - Komari; Ruswaji; Henny Mahmudah; Lilik Nurcholidah; Sandi Nasrudin Wibowo; Mesta Limbong (Universitas Pendidikan Ganesha, 2024)
Limitations of the leader's communication style with work performance, teacher job satisfaction, teacher commitment, and teacher motivation and teacher ability as a positive work culture have yet to show collective participation. The existence of harmony between theoretical expectations and reality urges a review to analyze leadership communication styles and teacher work culture towards collaborative management. The research method used is quantitative with a descriptive plan. The subjects were teachers and school leaders, totaling 310 respondents. Supervised data collection techniques by developing instruments based on research indicators. Technical analysis using SPSS Version 26.0 with correlation analysis. The results show that there is a positive and significant relationship between the level of the principal's basic tendency to power, the basis of expert power, the level of the basic tendency of the principal's coercive power, the level of the basic tendency of the principal's legitimate power, the principal's supervisory communication style, the teacher's work culture, the level of teacher competence, an organizational structure with a level of collaborative management at the level. The research conclusions show a negative and significant relationship between the age of leadership in secondary schools, the education level of school principals, and the level of collaborative management. The implications of this research can provide a positive picture and impact for leaders to communicate and collaborate massively and actively with teachers.